TEACHING ENGLISH ON THE BASIS OF PROFESSIONAL ORIENTATION AT THE FACULTIES OF NATURAL SCIENCES AS A PEDAGOGICAL PROBLEM (Spectrum Journal of Innovation, Reforms and Development, 2024)
This article focuses on the problems of students of the faculty of natural sciences in the formation of a level of professional orientation in English classes. It cites solutions to be found on this issue, with examples of a number of proposals. At the same time, the opinions of a number of researchers are studied.